REPLACEMENT OF CALCIUM FLUORIDE WITH BORATES AS CATALYST IN A VERTICAL RETORT PIDGEON PROCESS TO PRODUCE MAGNESIUM (A REVIEW) - Solaiman, Sylvester
The production of magnesium has been dominated by China. Chinese magnesium is produced by the silicothermic Pidgeon process. In the Pidgeon process, calcined dolomite, ferrosilicon as reductant, and calcium fluoride (CaF2) as a catalyst are charged into a vacuum horizontal retort. The retort is then heated externally to reduce the charged briquette. The Pidgeon process is characterized by its low capacity, relatively simple technology, batch process, low capital expenditure, and large emission of carbon dioxide from the calcination and reduction process. The low capacity is caused by the slow heat transfer rate from external heating, limiting the retort size. The slag has a small particle size that leads to dust formation. Due to the use of calcium fluoride, the slag also contains fluorine that its concentration is above the acceptable limit. Vertical retorts for the Pidgeon process can allow larger retort diameters. Borates such as B2O3 have been used to treat other fine metallurgical slags such as AOD slag from stainless steel production. This work aims to study the available vertical retort designs and examine the approach taken by each design to improve the Pidgeon process, and to study the effects caused by the replacement of CaF2 with borates as a catalyst for the Pidgeon process. This study starts with the collection of existing works and publications concerning the Pidgeon process. After that, collected works will be sorted and selected based on their relevance to this work. Then, the selected documents will be reviewed and analyzed to fulfill the objectives of this study. The reviewed documents and the phenomenon observed in each work will be compared to one another. If there exists some gap in the explanations provided by previous works, further search and review of references are suggested. Finally, conclusions are drawn from the review. Based on the conducted literature review, the following conclusions can be drawn: 1) Vertical retort designs for Pidgeon process have existed in at least a pilot-plant level application. However, there is a distinct lack of data needed to evaluate the relative performance of each design. 2) Vertical retort designs have the potential for space-saving, automation, and has a greater degree of reduction progress monitoring. 3) Full replacement of CaF2 with H3BO3 is not suggested, but a partial replacement is feasible. Partial replacement reduces fluorine content in magnesium slag and increased the particle size of magnesium slag. Calcium fluoride and borates seem to speed up reduction by forming a liquid slag phase that improves reactant transport. Several suggestions are made: 1) to experiment with lab-scale vertical Pidgeon process retort to gain first-hand data that can be compared with lab-scale horizontal retorts and 2) to investigate the cause of borates’ lower productivity compared to CaF2 when used as the catalyst for Pidgeon process.